On numerical Jacobi elliptic function solutions of the (1+1)-dimensional dispersive long wave equation by the decomposition method - İnç, Mustafa (Elsevier Science Inc, 2006)
In this paper, we consider to obtain approximate Jacobi elliptic function solutions of the (1 + 1)-dimensional long wave equation by using the Adomian decomposition method. As a results, we obtain the approximate solution and exact Jacobi elliptic function solutions of the (1 + 1)-dimensional long wave equation with initial conditions. The numerical results are compared with the known exact doubly periodic solutions. Most of the symbolic and numerical computations have been performed by using the Computer Algebra System-Mathematica. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Adomian decomposition method; the (1+1)-dimensional long wave equation; Jacobi elliptic function solution